Ecton processes in pulsed high-current electron beams; Proceedings of the 12th International Conference on High-power Particle Beams, Haifa, june 7-12, 1998; Vol. 1 - Mesyats G. A. Gennady Andreyevich (1998, 1998)
В фонде НТБ ТПУ отсутствует